Predictable changes in fish school characteristics due to a tidal turbine support structure. (October 2019) - Williamson, Benjamin; Fraser, Shaun; Williamson, Laura; Nikora, Vladimir; Scott, Beth
Abstract: There is uncertainty on the ecological effects of tidal stream turbines. Concerns include animal collision with turbine blades, disruption of migratory and foraging behaviour, attraction of animals to prey aggregating around turbines, or conversely displacement of animals from preferred habitat. This study used concurrent ecological and physical measurements to show the predictability of fish school characteristics (presence, school area and height above seabed) in a high energy tidal site across spring/neap, ebb/flood and daily cycles, and how this changed around a turbine structure. The rate of schools and school area per hour increased by 1.74 and 1.75 times respectively around a turbine structure compared to observations under similar conditions without a turbine structure. The largest schools occurred at peak flow speeds and the vertical distribution of schools over the diel cycle was altered around the turbine structure. While predictable attraction or aggregation of prey may increase prey availability and predator foraging efficiency, attraction of predators has the potential to increase animal collision risk. Predictable changes from the installation of turbine structures can be used to estimate cumulative effects on predators at a population level. This study can guide a strategic approach to the monitoring and management of turbines and arrays. Highlights: Fish school characteristics (rate, area, height) predictable over tidal & diel cycles. 1.74 times more schools/hour around a turbine support structure. Largest schools at peak flow speeds. 5.66 times more schools/hour downstream of turbine structure at flow speeds <1 m/s. Vertical distribution of schools over diel cycle changed around turbine structure.